2018
DOI: 10.1111/ped.13693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human breast milk on biological metabolism in infants

Abstract: The metabolic changes that occur during the postnatal weaning period appear to be particularly important for future health, and human breast milk is considered to provide the optimal source of nutrition for infants. Our previous studies examined the effect of feeding type on antioxidative properties, glucose and insulin metabolism, the lipid profile, metabolomics, and prostaglandin (PG) metabolism in term and preterm infants. A urinary marker of oxidative DNA damage (8-hydroxy-2'-deoxyguanosine) was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 59 publications
1
25
0
3
Order By: Relevance
“…Shoji and Shimizu found significant differences in urinary 8‐hydroxy‐2′‐deoxyguanosine, H 2 O 2 ‐induced oxidative damage in rat intestinal epithelial cell line (IEC‐6) cells, quantitative insulin sensitivity check index (QUICKI), atherogenic indices, urinary choline metabolites, and prostaglandin metabolites between breast‐fed and formula‐fed infants in early life. This showed that early feeding determines later health condition to some extent . Previous work by Ikeda et al .…”
supporting
confidence: 55%
“…Shoji and Shimizu found significant differences in urinary 8‐hydroxy‐2′‐deoxyguanosine, H 2 O 2 ‐induced oxidative damage in rat intestinal epithelial cell line (IEC‐6) cells, quantitative insulin sensitivity check index (QUICKI), atherogenic indices, urinary choline metabolites, and prostaglandin metabolites between breast‐fed and formula‐fed infants in early life. This showed that early feeding determines later health condition to some extent . Previous work by Ikeda et al .…”
supporting
confidence: 55%
“…The former is particularly suitable for studying nutrient intake or identifying food-specific biomarkers, while the latter is a reliable indicator of physiological response to food. Most of the metabolomics applications in neonatal nutrition research have been focused on deepening the knowledge about the HM composition, while a smaller number of investigations have assessed the impact of nutrition on infant metabolism [13][14][15][16][17]. Among these, to our knowledge, there is only one study on preterm infants that has explored the urinary metabolomics profile of infants fed with diets supplemented by two different levels of extra nutrients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been found measuring urinary F2-isoprostane [30] or MDA [31], stable biomarkers of oxidative damage to lipids. Moreover, feeding with BM is associated with a lower incidence of a variety of oxidative-stress related illnesses in premature infants [14]. These data provide evidence that BM is protective against oxidative damage in the high-risk population of preterm infants.…”
Section: Discussionmentioning
confidence: 59%
“…In this context, breastfeeding should be considered as the main measure to improve their antioxidant status. The benefits of BM against oxidative stress are demonstrated by the lower content of urine biomarkers in breastfed infants compared to those fed with formula, which has been attributed to the higher and more varied presence of antioxidants in BM [14]. The influence of gestational age on BM antioxidants is controversial.…”
Section: Introductionmentioning
confidence: 99%